On coupled systems of Lidstone-type boundary value problems - de Sousa, Robert; Minhós, Feliz; Fialho, João (Mathematical Modelling and Analysis, 2021)
This research concerns the existence and location of solutions for coupled system of differential equations with Lidstone-type boundary conditions. Methodology used utilizes three fundamental aspects: upper and lower solutions method, degree theory and nonlinearities with monotone conditions. In the last section an application to a coupled system composed by two fourth order equations, which models the bending of coupled suspension bridges or simply supported coupled beams, is presented.